POLA PERGERAKAN “PASAR TIBAN” KOTA PEKALONGAN - Dwi Hartini; Jamilla Kautsary (Jurnal Planologi, 2017)
Community activities in the commercial sector have an impact on the economic development of the city which is the influence of the city development into a town center trade. one of which is the existence of market tiban. A consequently of market activity tiban cause problems such as disrupting the flow of traffic as well as general merchandise facilities held alongside a road or along the corridor on the right or left, so that it is distrub traffic flow. The purpose of this study to find patterns in the market movement tiban Pekalongan. In this study, use a qualitative descriptive approach rationalistic. To achieve the goal of the analysis is then performed 3 analyzes the spatial pattern of movement does not include time tiban market movements, modes of movement, and activity systems analysis contained in tiban market, analysis of spatial movement patterns include cross- sectional analysis of the road corridor, stall dimensions, system settings tiban market, and movement patterns tiban market, and analyzes the factors behind the choice of location which is distance tiban market location, location tiban traders in the market, the similarity of merchandise, consumer offerings, the number of visitors, and mindset. Based on the analysis the pattern of market movements in Pekalongan tiban following reasons traders in making trading location and tiban market always occur on the same day and location. The recommendations contained in this study the need for regulation and supervision of the government in market activity in Pekalongan to minimize the problems effect of market activity tiban. There needs to be awareness of traders and buyers in the market tiban activities to keep abreast of the prevailing order in Pekalongan. There a good management of community market tiban to be organized and able to maximize the benefits of market tiban as evening entertainment for the citizens of Pekalongan.